MERAJUT STRATEGI DAN “MERUBAHNYA” MENJADI AKSI (KAJIAN BUKU : “STRATEGY MAPS” oleh KAPLAN & NORTON, DAN CRAFTING AND EXECUTING STRATEGY oleh THOMPSON & STRICKLAND) - Rizal Rivai, Alimuddin (Fokus Ekonomi, 2006)
Strategies are important for an organization. Basic framework in the study of management strategy is that the strategy is built base on the right and proper organization’s situation and condition. However, empirically, it is failvery often in the implementation. That’s why the execution strategy level requires the correct socialized, structured, and systematically process which is done in the right time. The strategy will be useful for a company if it isexecuted consistently by all management divisions in organization. Some books like “Strategy Maps” by Kaplan and Norton and “Crafting and Executing Strategy” by Thompson and Strickland can guide us to implement strategies which are chosen to be the action to obtain the company’s goal.Keywords: Strategy Map, Intangible Assets, Tangible Assets, Crafting and Executting Strategy.